Performance of Employees in The Human Resources and General Affairs Directorate General of Land Transportation Ministry Of Transportation - Ana Rosiana; Istiatin; Sudarwati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine and explain the effect of compensation, workload, work experience and competence on the performance of employees of the HR Department of the Ministry of Transportation, Jakarta. The population of this study was 30 employees of the HR Department of the Ministry of Transportation, Jakarta with a saturated sample. Data collection using a questionnaire. Data analysis techniques using the Multiple Linear Analysis method. The results of the study showed that compensation, workload, work experience and competence on the performance of employees of the HR Department of the Ministry of Transportation, Jakarta have a positive and significant effect by contributing to performance of 71.7% while the remaining 28.3% is explained by other variables not proposed in this study. Suggestions from this study, employees of the HR Department of the Ministry of Transportation Jakarta can improve their competence and work experience in the appropriate workload level so that leaders will provide appropriate compensation for the performance carried out.